Analisis Kritis Peran Rencana Tata Ruang Wilayah (RTRW) sebagai Instrumen Perlindungan Lingkungan Hidup - Amelia, Juni Riski (Universitas Sang Bumi Ruwa Jurai, 2024)
Regional Spatial Planning (RTRW) is a spatial planning instrument that regulates land use and spatial patterns of an area with a focus on environmental aspects. RTRW has an important role in creating integration between regional development and environmental preservation. This is reflected in development policies which must pay attention to environmental protection aspects as a whole. However, differences between RTRW theory and its implementation in the field may occur, This research uses a juridical-normative research method, while the data analysis method used is qualitative and the data collection tool used is document study. The research results show that decision no. 124/G/LH/2016/PTUN-BDG regarding the construction of a Steam Power Plant in Cirebon Regency emphasizes the importance of compliance and enforcement of environmental laws and solutions such as increasing awareness, monitoring and law enforcement. Resolving environmental disputes involving various methods is a crucial step in protecting the environment. The importance of community participation in environmental impact analysis and dispute resolution is also emphasized